Voracious transformation of a common natural resource into productive capital - Van der Ploeg, R (University of Oxford, 2008)
We analyze a power struggle about the control of natural resources where competing factions in society have a private stock of financial assets and a common stock of natural resources with inadequately defined private property rights. We solve a dynamic common-pool problem and obtain political economy variants of the Hotelling rule for resource depletion and the Hartwick saving rule necessary to sustain constant consumption in an economy with exhaustible natural resources. The rate of increase in the price of natural resources and resource depletion are faster than demanded by the Hotelling rule. As a result, the country substitutes away from resources to capital too rapidly so that it saves and invests more than a homogenous society. The power struggle boosts output, but depresses aggregate consumption and social welfare. Genuine saving is nevertheless zero in a fractionalized society, since the too rapid depletion of natural resources is exactly in line with the too rapid accumulation of physical capital. World Bank measures of genuine saving are likely to be over-estimated. This exacerbates the puzzle of why many resource-rich countries experience negative genuine saving rates.